PENGARUH PEMBIAYAAN MURABAHAH DAN MUDHARABAH TERHADAP LABA PADA BANK SYARIAH MANDIRI PERIODE 2012-2020 - Endang Rahmat; M. Kaharudin Yasin (Jurnal Ekonomi Rabbani, 2021)
The purpose of this study is to find out and analyze how much influence partially murabahah financing has on profits, how much influence partially mudharabah financing has on profits, and also to find out how much influence murabahah and mudharabah financing have on profits simultaneously. This study uses a quantitative descriptive method with multiple linear regression analysis tools. Based on the results of the tests carried out, it shows that the murabahah financing variable has a partially significant effect on profits, the mudharabah financing variable does not have a partial effect on profits, the murabahah and mudharabah financing variables have a simultaneous effect on profits at PT. Bank Syariah Mandiri period 2012-2020. The purpose of this study is to find out and analyze how much influence partially murabahah financing has on profits, how much influence partially mudharabah financing has on profits, and also to find out how much influence murabahah and mudharabah financing have on profits simultaneously. This study uses a quantitative descriptive method with multiple linear regression analysis tools. Based on the results of the tests carried out, it shows that the murabahah financing variable has a partially significant effect on profits, the mudharabah financing variable does not have a partial effect on profits, the murabahah and mudharabah financing variables have a simultaneous effect on profits at PT. Bank Syariah Mandiri period 2012-2020.